2019
DOI: 10.1371/journal.pone.0218867
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Ascaris spp. infecting humans and pigs in distinct Brazilian regions, as revealed by mitochondrial DNA

Abstract: In this study, we assessed the genetic diversity of Ascaris lumbricoides / Ascaris suum circulating in humans and pigs, exploring potential zoonotic cycles in endemic areas in Brazil. We carried out cross-sectional surveys in four municipalities: Santa Isabel do Rio Negro (SIRN-AM) (n = 328); Nossa Senhora de Nazaré (NSN-PI) and Teresina (TER-PI) (n = 605 and n = 297, respectively); and Cachoeiras de Macacu (CAM-RJ) (n = 543). We also studied 61 fecal samples/adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
(57 reference statements)
4
16
0
1
Order By: Relevance
“…Population genetic studies of A. lumbricoides have drawn varying conclusions about whether zoonotic transmission is frequent ( Anderson and Jaenike, 1997 ; Dutto and Petrosillo, 2013 ; Nejsum et al, 2012 ; Nejsum et al, 2005a ). Some studies have shown that cross-species transmission occurs between pigs and humans living in close proximity ( Anderson, 1995 ; Betson et al, 2014 ; Miller et al, 2015 ; Monteiro et al, 2019 ; Nejsum et al, 2005b ; Peng and Criscione, 2012 ; Sadaow et al, 2018 ; Takata, 1951 ; Zhu et al, 1999 ). This is especially common in non-endemic regions, probably because zoonotic transmission is less likely to be identified in areas where human-to-human transmission is common.…”
Section: Introductionmentioning
confidence: 99%
“…Population genetic studies of A. lumbricoides have drawn varying conclusions about whether zoonotic transmission is frequent ( Anderson and Jaenike, 1997 ; Dutto and Petrosillo, 2013 ; Nejsum et al, 2012 ; Nejsum et al, 2005a ). Some studies have shown that cross-species transmission occurs between pigs and humans living in close proximity ( Anderson, 1995 ; Betson et al, 2014 ; Miller et al, 2015 ; Monteiro et al, 2019 ; Nejsum et al, 2005b ; Peng and Criscione, 2012 ; Sadaow et al, 2018 ; Takata, 1951 ; Zhu et al, 1999 ). This is especially common in non-endemic regions, probably because zoonotic transmission is less likely to be identified in areas where human-to-human transmission is common.…”
Section: Introductionmentioning
confidence: 99%
“…Further insight for the identification of correlates of protection could be provided by the study of humoral and cellular mechanisms that confer protection in animal models A. suum is the infectious agent of porcine ascariasis, which substantial and is closely related to the human helminth A. lumbricoides. Both parasites show striking similarities in their morphology, biology and genetics with both exhibiting anthropozoonotic potential (9)(10)(11). Accordingly, it has been suggested that the two parasites actually belong to the same species (12), with A. suum representing an excellent model to study the common human nematode.…”
Section: Introductionmentioning
confidence: 99%
“…Escolheu-se aleatoriamente dois grupos de parasitos, Ascaris lumbricoides e os ancilostomídeos, para questionar especifi camente sobre seus ciclos de vida e formas No entanto, faz-se imprescindível enfatizar sobre o potencial zoonótico de Ascaris sp., principalmente relacionando aos cuidados na criação de suínos (MONTEIRO et al, 2019). À medida que conhecem sobre esse parasito, promovem a redução na transmissão, reinfecção e incentivam a família a comportamentos saudáveis.…”
Section: Caracterização Do Público E Grau De Conhecimento Sobre Parasunclassified